Analysis of the Implementation of Zakat, Infaq and Sadaqah (ZIS) Accounting In terms of PSAK 101 and PSAK 109 - Fatmawatie, Naning (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2023)
The scope of accounting for zakat, infaq and shadaqah (ZIS) that is the recognition, record and present of the financial statements of the ZIS managing institution. Accountability is carried out as a form of accountability which explains and describes the performance of an institution. This study aims to analyze the application of ZIS Accounting from the perspective of PSAK 101 and PSAK 109. This type of research is descriptive qualitative. The data used are primary data and secondary data. The results of the study explained that the application of ZIS Accounting in terms of PSAK 109 shows that this institution has not fully implemented this article, especially in the fair assessment of infaq and shadaqah receipts without cash, then the distribution of cash comes from infaq and shadaqah. In presenting the financial statements as well as originating from the details of the funds received from zakat, whether individuals or entities in the report on changes in funds have not implemented them. In addition, there is no explanation for financing activities in the statement of cash flows. Then implementation of accountability in the figures in financial reports as well as reporting has almost completely implemented PSAK 101. In this case, accountability indicators and the amount of financial reporting to donors have been implemented.